2003
DOI: 10.1038/sj.onc.1206207
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin antagonist suppresses in vivo growth of human pancreatic cancer cells in SCID mice by suppressing angiogenesis

Abstract: Since it is reported that adrenomedullin (AM) upregulated by hypoxia inhibits hypoxic cell death, we examined the effects of AM antagonist (AM C-terminal fragment; AM(22-52)) on the growth of pancreatic cancer cells. We, for the first time, demonstrated that AM antagonist significantly reduced the in vivo growth of the pancreatic cancer cell line. Immunohistochemical analysis demonstrated that the mean diameter of blood vessels was significantly smaller in the tumor tissues treated with AM antagonist than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 24 publications
3
103
1
Order By: Relevance
“…The HIF target adrenomedullin was shown to promote physiological and pathological angiogenesis in vitro and in animal models (49)(50)(51). ADM signals angiogenesis by binding calcitonin-receptor-like receptor, which is widely expressed on normal and hypoxic endothelial cells (49,52).…”
Section: Discussionmentioning
confidence: 99%
“…The HIF target adrenomedullin was shown to promote physiological and pathological angiogenesis in vitro and in animal models (49)(50)(51). ADM signals angiogenesis by binding calcitonin-receptor-like receptor, which is widely expressed on normal and hypoxic endothelial cells (49,52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in some cancers, AM expression is associated with vascular density and endothelial cell proliferation (Hague et al 2000). In vitro studies have shown the AM receptor antagonist AM 22-52 was able to abrogate tumor formation of a pancreatic tumor cell line suggesting a role for AM in this cancer (Ishikawa et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the studies for vascular endothelial growth factor, the density of blood vessels in the AM antibody-treated tumors was also decreased, supporting the roles for AM in angiogenesis, vasculogenesis and/or vessel stabilization (Zhao et al, 1998;Ouafik et al, 2002;FernandezSauze et al, 2004). In good agreement, Ishikawa et al (2003) demonstrated that the AM antagonist (hAM (22-52)-NH 2 ) inhibited pancreatic cancer cell growth in vivo by suppressing tumor vascular development.…”
Section: Introductionmentioning
confidence: 69%